Hubungan Antara Kepercayaan Diri dengan Penyesuaian Sosial pada Siswa Kelas IX SMPN 39 Semarang - Prihatini, Salma; Handayani, Arri; Mujiyono (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Social adjustment is very important for adolescents, students are no longer introverted and feel lonely, because they can adjust to their environment. Having good self-confidence individuals can behave as expected, are not selfish, want to involve themselves in a wider environment without needing encouragement from others, dare to face various challenges optimistically, and always feel happy so that the people around them will feel their cheerful energy. One of the factors that influence individual social adjustment is self-confidence. the process of achieving positive social adjustment is characterized by trust in oneself, others, and everything outside oneself. This study aims to determine the relationship between self-confidence and social adjustment in class IX students of SMP N 39 Semarang. In this study using quantitative methods with the type of correlation research. The population in this study were 288 students. The sample in this study was 65 students determined by cluster random sampling technique. Based on the Pearson product moment correlation test obtained r count of 0.594, while r table for a sample size of 65 is 0.240, it can be concluded that there is a significant relationship between social adjustment and self-confidence at SMP N 39 Semarang. The positive relationship means that if social adjustment then low self-confidence behavior and vice versa if low social adjustment then high self-confidence behavior.